Palatine rugoscopy - literature review (Research, Society and Development, 2022)
The palatal rugoscopy identification technique was developed by the Spanish researcher Trobo-Hermosa in 1930. This human identification methodology uses palatal rugosities, in view of the anatomy of the palate being indistinguishable and immutable throughout life. Objective: analyze the importance of palatal rugoscopy for human identification. Methodology: An integrative literature review was carried out, with a reflective theoretical approach in PubMed and the Virtual Health Library between 2016 and 2021. Results: In the initial screening, 1574 articles were found, mostly in English. Of the total of these articles, 28 were excluded because they did not correspond to the objective of the research and the others were grouped into three themes: Reliability of the use of palatal wrinkles dimensions in human identification; Palatal Rugoscopy and sexual dimorphism: Palatoscopy: in Brazil and in the World. Conclusion: Although many current studies demonstrate the discriminating power of palatal wrinkles in forensic identification, there are limitations for this technique to be used in practice, given the dependence on archiving patients' antemortem documents, be they images, 3D scanning, models plaster and/or paper registration.